Tekst van Domela, 11 november 1915, op achterkant. Zie ook BG S3/11, BG S8/13, BG S8/29 en BG S8/31 - Kok, J.J.,
Tekst van Domela, 11 november 1915, op achterkant. Zie ook BG S3/11, BG S8/13, BG S8/29 en BG S8/31.